AN 4: Andes coordination project - Saravia, Miguel; Bievre, B. de; Fernández Baca, E.; Acosta, L.; Lizarraga, L. (CGIAR Challenge Program on Water and Food, 2010)
The Basin Leader leads this project team which is responsible for coherence of the overall BDC research program by ensuring BDC research remains problem- opportunity- and impact-focused. For the duration of the project, the Basin Leader will work for the CPWF, through a secondment arrangement to be negotiated with CONDESAN. The Basin Leader will report to both the CPWF Research and Innovation & Impact Directors, and will be supervised by the appropriate CPWF Director among them